2018
DOI: 10.1159/000493470
|View full text |Cite
|
Sign up to set email alerts
|

Dialysate Calcium Concentration below 3.0 mEq/L Is Not Associated with Improved Outcomes in the Japanese Dialysis Outcomes and Practice Patterns Study

Abstract: Background: Abnormal chronic kidney disease-mineral and bone disorder (CKD-MBD) markers have been associated with adverse outcomes in hemodialysis (HD) patients. Dialysate calcium concentration (D-Ca) likely influences serum calcium and phosphorus levels. Optimal D-Ca level remains unclear. We hypothesized that higher D-Ca is associated with cardiovascular events and mortality among Japanese HD patients. Methods: Enrollment data of chronic HD patients in the prospective observational study JDOPPS, phases 1–5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…However, the association of D-Ca and the combined outcome was again not significant. Similar to our results, another observational study derived from the Japanese Dialysis Outcomes and Practice Patterns Study reported that the difference in D-Ca was not related to the survival based on the results of 9,201 patients with a median follow-up of 2.03 years [ 16 ]. Thus, the low statistical power does not fully explain the neutral results on the D-Ca in this range and clinical outcomes in this study.…”
Section: Discussionsupporting
confidence: 86%
“…However, the association of D-Ca and the combined outcome was again not significant. Similar to our results, another observational study derived from the Japanese Dialysis Outcomes and Practice Patterns Study reported that the difference in D-Ca was not related to the survival based on the results of 9,201 patients with a median follow-up of 2.03 years [ 16 ]. Thus, the low statistical power does not fully explain the neutral results on the D-Ca in this range and clinical outcomes in this study.…”
Section: Discussionsupporting
confidence: 86%
“…18 Although one dialysate calcium concentration of 2.75 mEq/L became available in 1993 in Japan, 19 any dialysate calcium concentrations below 3.0 mEq/L were unlikely to have a clinically significant effect on patient prognosis. 20 Unlike in other countries, where singlepatient dialysis fluid delivery systems have been used based on each patient's condition, a central dialysis fluid delivery system has been adopted for the past 45 years in Japan with the dialysate calcium concentration determined based on the policy of the medical facility. 21 Because evocalcet and cinacalcet both lower the serum calcium concentration, their efficacy and safety may be affected by the concentration of dialysate calcium.…”
Section: Introductionmentioning
confidence: 99%